Kontestasi Persaingan Program Acara Berita dalam Bisnis Media Televisi - Rahayu Rahmadini (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
This paper aims to explain the contestation among news programs in deal with a television media business. This research appropriated the Media Economic Theory derived from Vincent Moscow and the Theory of Media. The research uses a postpositivism paradigm. This paper follows a descriptive-qualitative approach. Findings: the contestation among news programs has a good and quality competition of television media business. And also, this research explains how broadcastiong station strategy can produce a program to reach an success and beyond a rivality in similar program that propose by the other broadcasting station.